2017
DOI: 10.1111/crj.12648
|View full text |Cite
|
Sign up to set email alerts
|

Use of TBAg/PHA ratio in distinguishing tuberculoma from cancer in solitary pulmonary nodule or mass

Abstract: Calculation of the TBAg/PHA ratio might provide a useful non-invasive tool for distinguishing tuberculoma from cancer in patients with a solitary pulmonary nodule or mass in TB-endemic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…We have first emphasized that the substrate incubation time, peripheral blood mononuclear cell counting, and the setting of ELISPOT reader parameters (such as exposure time and sensitivity) are the key factors affecting SFC results of antigen and PHA in T-SPOT assay (20,37). In addition, we first put forward the concept of TBAg/PHA ratio and found that the performance of TBAg/PHA ratio is better than directly using T-SPOT antigen results not only in distinguishing active tuberculosis (ATB) from latent tuberculosis infection (LTBI) but also in differential diagnosis of pulmonary and extrapulmonary TB (20,26,(37)(38)(39)(40)(41). We also first put forward that 1 × 10 5 was the optimal number of pleural fluid mononuclear cells for performing pleural fluid T-SPOT and that the mean spot size of ESAT-6 has an adjunctive role in the diagnosis of ATB (42,43).…”
Section: 18%mentioning
confidence: 99%
“…We have first emphasized that the substrate incubation time, peripheral blood mononuclear cell counting, and the setting of ELISPOT reader parameters (such as exposure time and sensitivity) are the key factors affecting SFC results of antigen and PHA in T-SPOT assay (20,37). In addition, we first put forward the concept of TBAg/PHA ratio and found that the performance of TBAg/PHA ratio is better than directly using T-SPOT antigen results not only in distinguishing active tuberculosis (ATB) from latent tuberculosis infection (LTBI) but also in differential diagnosis of pulmonary and extrapulmonary TB (20,26,(37)(38)(39)(40)(41). We also first put forward that 1 × 10 5 was the optimal number of pleural fluid mononuclear cells for performing pleural fluid T-SPOT and that the mean spot size of ESAT-6 has an adjunctive role in the diagnosis of ATB (42,43).…”
Section: 18%mentioning
confidence: 99%
“…The TBAg/PHA ratio is a specific indicator for TB diagnosis. Apart from distinguishing between ATB and LTBI it can also be used to discriminate TB from other respiratory diseases such as lung cancer, bacterial pneumonia and fungal pneumonia (Wang et al, 2018a, Wang et al, 2020. Meanwhile, iron metabolism indexesincluding SI, SF and TFhave also been reported to have potential value in differentiating ATB from other lung illness such as chronic obstructive pulmonary disease and respiratory tract infections (Dai et al, 2019, Jacobs et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…(I) The ratio of TB-specific antigen (TBAg) to phytohaemagglutinin (PHA) (TBAg/PHA): the larger of the ESAT-6/PHA and CFP-10/PHA of T-SPOT assay is defined as the TBAg/PHA ratio [ 78 ]. We have found that calculation of the TBAg/PHA ratio of the T-SPOT assay can increase the specificity of this assay for diagnosis of active TB [ 78 , 79 , 80 , 81 , 82 , 83 ]. The theoretical basis is that TBAg/PHA ratio can eliminate the impact of individual immune variation on a T-SPOT assay.…”
Section: Immunological Diagnosismentioning
confidence: 99%